2013
DOI: 10.1177/1934578x1300801101
|View full text |Cite
|
Sign up to set email alerts
|

Three New Iridoid Glucoside Salts from Hedyotis tenelliflora Growing in Vietnam

Abstract: Three new sodium salts of iridoid acids, deacetylasperulosidic acid sodium salt (1), teneoside D (2), and teneoside E (3) were isolated from the leaves of Hedyotis tenelliflora Blume (Rubiaceae), together with seven known iridoids, 6α-hydroxygeniposide (4), 6β-hydroxygeniposide (5), 6-O-methyldeacetylasperulosidic acid methyl ester (6), 6-O-methylscandoside methyl ester (7), 6α-methoxygeniposidic acid (8), daphylloside (9), and mollugoside methyl ester (10). Their chemical structures were elucidated by 1D and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The 13 C-NMR data of 4 ( Table 1 ) was found to be comparable with that of the scandoside [ 29 ], which contained a -COOH group, except for a significant deshielding of C-4 (+5.4 ppm) and C-11 (+3.8 ppm) and shielding of C-3 (−4.1 ppm) in 4 that verified the anionization of the C-4 carboxyl group. The anionization effect has been reported to cause a deshielding impact on 13 C-NMR resonances close to the negative charge [ 30 , 31 ]. The stereochemistry of 4 , assigned by the NOESY experiment ( Figure 6 ), was the same as that of scandoside.…”
Section: Resultsmentioning
confidence: 99%
“…The 13 C-NMR data of 4 ( Table 1 ) was found to be comparable with that of the scandoside [ 29 ], which contained a -COOH group, except for a significant deshielding of C-4 (+5.4 ppm) and C-11 (+3.8 ppm) and shielding of C-3 (−4.1 ppm) in 4 that verified the anionization of the C-4 carboxyl group. The anionization effect has been reported to cause a deshielding impact on 13 C-NMR resonances close to the negative charge [ 30 , 31 ]. The stereochemistry of 4 , assigned by the NOESY experiment ( Figure 6 ), was the same as that of scandoside.…”
Section: Resultsmentioning
confidence: 99%
“…Since then, glucan (Cui et al, 2006), naphthoquinones and cyclotides (Ding et al, 2014) have been obtained from the species of this genus. A comparative chemotaxonomy study of different species demonstrated that iridoids are the predominant and characteristic constituents of genus Hedyotis (Chen et al, 2005;Van Long et al, 2013).…”
Section: Introductionmentioning
confidence: 99%